LEGAL ANALYSIS OF LEGAL RISK MANAGEMENT IN HUMAN RESOURCE MANAGEMENT AND ITS IMPACT ON COMPANY PERFORMANCE - Jumardin; M. Amsyahar; Alamsyah; Astri Aryanti Amsyahar (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the application of legal risk management in human resource management and examine its impact on company performance. The issues studied include the forms of legal risks that arise in human resource management practices, efforts to handle them based on applicable laws and regulations, and their impact on achieving company goals. The research method used is normative legal research with a statutory, conceptual, and analytical approach. Data collected comes from primary, secondary, and tertiary legal materials, which are then analyzed qualitatively. The results of the study indicate that legal risks in human resource management can include employment disputes, violations of workers' rights, and administrative and criminal sanctions due to non-compliance with legal provisions. The application of good legal risk management, including identification, assessment, handling, and monitoring of risks, has been proven to minimize the occurrence of legal disputes and losses. Furthermore, this has a positive impact on improving company performance, including through the creation of a conducive work climate, increased employee productivity, and maintained business image and sustainability. This study concludes that legal risk management is a strategic aspect that is inseparable from human resource management, so it needs to be strengthened through the preparation of legally compliant internal policies and increasing legal awareness of all parties in the company.